Declaration of Tax Information in Constitutional Court Cases in the Czech Republic - Sejkora, Tomáš (Public Governance, Administration and Finances Law Review, 2019)
This contribution is focused on the trend to demand various declaration of taxable persons via specific forms issued based only on the wide and vague authorisation of the Ministry of Finance of the Czech Republic. The aim of this paper is to familiarise readers with the relevant Czech regulation and case law of the Czech Constitutional Court and to provide conclusions evaluating this case law and legislation. The beginning of this paper is devoted to respective provisions of the Tax Procedure Code, Charter of Fundamental Rights and Freedoms, Act on VAT and Act on Transactions evidence. Then, the part dealing with the development of the Constitutional Court approach evaluating the practice of the tax administration follows. Finally, the author provides his conclusions estimating future development in this issue. Scientific methods used in this paper are analysis, induction, deduction and description. The aim of the contribution is therefore the evaluation how the recent case law will affect the current legislation and what steps should be made by the Czech Parliament.